2021
DOI: 10.1016/j.jcjp.2021.100021
|View full text |Cite
|
Sign up to set email alerts
|

A review of bone marrow lesions in the arthritic knee and description of a technique for treatment

Abstract: Introduction: Subchondral bone pathology includes a wide range of pathologies, such as osteoarthritis, spontaneous insufficiency fractures, osteonecrosis, transient bone marrow lesions syndromes, and trauma. They show typical magnetic resonance imaging (MRI) findings termed bone marrow lesions (BMLs). However, the etiology and evolution of BMLs in multiple conditions remains unclear. There is still no gold standard treatment protocol in treating BMLs in the knee, and a variety of treatment modalities have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The small dowels of autologous bone are injected into the affected area to fill the intertrabecular space, thereby inducing improved bone remodeling and delivering additional supportive and biologically active tissue to the subchondral lesion [35].…”
Section: Discussionmentioning
confidence: 99%
“…The small dowels of autologous bone are injected into the affected area to fill the intertrabecular space, thereby inducing improved bone remodeling and delivering additional supportive and biologically active tissue to the subchondral lesion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that some OA features only detectable by MRI, including bone marrow lesions (BMLs) play a role in structural OA incidence and progression and may be present before cartilage damage occurs [6][7][8] . BMLs are associated with knee pain and meniscal damage and extrusion 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…First, we have an article by ICRS past-president Professor Alberto Gobbi and colleagues entitled "A Review of Bone Marrow Lesions in the Arthritic Knee and Description of a Technique for Treatment . " 1 In this article, the authors discuss the etiology and types of bone marrow lesions, as well as the biology and biomechanics of these lesions along with relevant anatomy. Treatment options for these difficult entities are also reviewed, including a description of the technique and benefits of a novel minimally invasive procedure to induce bone remodeling referred to as Osteo-Core-Plasty.…”
mentioning
confidence: 99%